ANALISIS PENERAPAN MODEL PROJECT BASE LEARNING DALAM MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN ESTIMASI BIAYA KONSTRUKSI - Raymond Christ Opel Samosir (CV. Adiba Aisha Amira, 2024)
The Project Based Learning (PjBL) learning model is an approach that focuses on Higher Level Thinking Skills (HOTS) where students are actively involved in solving problems both individually and in groups. This model involves a series of structured stages and produces a product that must be presented. Construction Cost Estimation (EBK) is one of the subjects in the Design Modeling and Building Information (DPIB) program at Vocational Schools which requires an understanding of bestek drawings, calculating work volumes, unit price analysis of work, implementation schedules, and S curves. This analysis aims to assess the impact of using the HOTS-based PjBL model on student learning outcomes in EBK subjects.